2006
DOI: 10.1245/aso.2006.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Primary Tumor Extirpation in Breast Cancer Patients Who Present With Stage IV Disease and an Intact Primary Tumor

Abstract: Removal of the intact primary tumor for breast cancer patients with synchronous stage IV disease is associated with improvement in metastatic progression-free survival. Prospective studies are needed to validate these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
152
0
26

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 250 publications
(199 citation statements)
references
References 20 publications
13
152
0
26
Order By: Relevance
“…Some studies reported that the use of chemotherapy was lower among women who underwent surgery [9]. In contrast, other studies found that these women were more likely to receive chemotherapy, hormonal therapy, or both than patients who did not have surgery [8,13]. In one study patients, who received surgery were significant older than patients who were not treated with surgery [12].…”
Section: Multivariate Analyses From the Individual Studiesmentioning
confidence: 93%
See 3 more Smart Citations
“…Some studies reported that the use of chemotherapy was lower among women who underwent surgery [9]. In contrast, other studies found that these women were more likely to receive chemotherapy, hormonal therapy, or both than patients who did not have surgery [8,13]. In one study patients, who received surgery were significant older than patients who were not treated with surgery [12].…”
Section: Multivariate Analyses From the Individual Studiesmentioning
confidence: 93%
“…In most studies, the patients who had surgery were significantly younger when compared to the patients who did not had surgery [7-10, 12, 13]. These patients had also smaller primary tumors and more often just one metastatic localization [8,9,12,13]. Some studies reported that patients who had surgery also had less extensive regional disease [8,15].…”
Section: Multivariate Analyses From the Individual Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, which was based In the current study, we analyzed the changes in prognosis for more than 8,000 patients with primary distant metastatic breast cancer diagnosed between 1995 and 2008 and followed until 2010, using nation-wide data of the Netherlands Cancer Registry. As described above, surgery of the primary tumor is not standard treatment in these patients, though several retrospective studies have shown an improvement in overall survival in patients who have received breast surgery [5][6][7][8][9][10][11]. Therefore, we also analyzed the impact of surgical resection of the primary breast tumor, besides the role of systemic treatment.…”
Section: Introductionmentioning
confidence: 99%